SOSIALISASI PANGAN FUNGSIONAL DARI SUMBER DAYA LAUT KEPADA MASYARAKAT PESISIR SAMBOANG KECAMATAN BONTOTIRO - Hasan, Tahirah; Nurdaya, Nurdaya (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2023)
Back to nature is a term about returning to nature both in terms of medicine and in terms of food and drink. The sea is a food resource that provides many sources of nutrients such as protein, carbohydrates and fats, but it has not yet been utilized optimally by local communities. The aim of this activity is to increase the understanding of the Samboang coastal community in utilizing marine resources such as fish, seaweed, shellfish and several other types of marine biota. The results of the activity evaluation showed that the activity participants had expertise in selecting food for health from the sea. The activity was attended by 20 local people, delivered using a lecture method containing material relevant to the topic. Backt to nature, nutrition samboang, sea